Analisis kemampuan berpikir kritis matematis ditinjau dari resiliensi matematis mahasiswa pendidikan teknik informatika dan komputer - Ade Evi Fatimah; Fitriani Fitriani (Mahesa Research Center, 2021)
This study aims to determine the students' mathematical critical thinking abilities in terms of their mathematical resilience. The subjects of this study were students of Informatics and Computer Engineering Education STKIP Al Maksum in discrete mathematics courses, totaling 37 students. The research instrument used in the form of mathematical critical thinking ability test questions and student mathematical resilience questionnaires. The research method used is a correlational method with a quantitative approach. Then the data were analyzed using simple linear regression. The results showed that the mathematical critical thinking ability based on the mathematical resilience of the students of the Computer Informatics Engineering Education Study Program, STKIP Al Maksum, had a positive effect of 79.9%.